Modern shopping cart with automatic billing system using load sensor - Kavitha, D; ., . (International Journal of Engineering and Technology, 2018)
A survey of peopleâ€™s shopping habits has been completed recently and they've come up with the top 10 list of the things that people hate when supermarket shopping. These figures were taken from a survey of 2500 people on their supermarket shopping habits. There is no surprise on the number one issue - It was long queues at the check-outs with 62 per cent of the people surveyed stating this to be their big issue when shopping in a super market. So we have enhanced an idea to avoid long queues by providing SMART TROLLEY. Here we have provided a barcode reader and digital display in order to display the total amount of the shopping. It has two additional functionalities to make this Trolley more efficient. It has a LOAD CELL to detect the mal practice. In addition, we have provided IN SWITCH and OUT SWITCH for customer ease of use.Â Â